2, 3, 7, 8-Tetrachlorodibenzo-p-dioxin potential impacts on peripheral blood mononuclear cells of endometriosis women. (February 2022) - Tanha, Mahsa; Bozorgmehr, Mahmood; Shokri, Mohammad-Reza; Edalatkhah, Haleh; Tanha, Mahya; Zarnani, Amir-Hassan; Nikoo, Shohreh
Highlights: PBMCs of endometriosis patients express lower levels of AHR and IDO1 genes compared to those of normal individuals. TCDD increases the expression of AHR, IDO1 and FOXP3 genes in endometriosis compared to non-endometriosis PBMCs. In response to TCDD treatment, endometriosis PBMCs produce higher levels of kynurenine and IL-6. Abstract: Endometriosis happens following the implantation of endometrial-derived tissues outside the uterine cavity. It has been suggested that 2, 3, 7, 8-Tetrachlorodibenzo-p-dioxin (TCDD) is involved in endometriosis development. Furthermore, aryl hydrocarbon receptor (AHR), as a TCDD receptor, has been demonstrated to regulate immune responses. Nonetheless, data regarding the mechanisms, through which TCDD influences the immune system in endometriosis, are still inconclusive. Therefore, frequency of regulatory T cells (Tregs) and the expression of FOXP3, AHR and indoleamine 2, 3-dioxygenase 1 ( IDO1 ) from endometriosis and non-endometriosis individuals were investigated in the absence and presence of TCDD; also, the concentration of IL-6 and kynurenine in the supernatant of cultures was assessed. The impact of TCDD-treated PBMCs on the migration capacity of menstrual blood-derived stromal stem cells (MenSCs) and monocyte chemoattractant protein-1 (MCP-1) and IL-6 production was determined. Here, we found that AHR and IDO1 expression levels were lower in endometriosis PBMCs; however, TCDD treatment increased AHR, FOXP3, IDO1, IL-6, and Treg levels in the endometriosis group (P ≤ 0.05−0.0001). TCDD-treated PBMCs increased the migration capacity of MenSCs and up-regulated MCP-1 and IL-6 levels in the PBMCs/MenSCs co-culture (P ≤ 0.01−0.0001). In conclusion, these results shed light on the probable mechanisms, through which AHR activation by chemical toxicants can impact inflammatory immune mediators involved in the development of endometriosis; also, these data support the idea that TCDD could promote endometriosis progression.